Peran Konsep Missio Dei dalam Konteks Gereja Lokal - Anggita Aiba (PASOLO: Jurnal Ilmu Teologi dan Pendidikan Kristen, 2026)
This article reviews the concept of mission Dei as a theological basis for the mission of the church, especially in the context of the local church. Mission Dei emphasizes that the mission comes from God himself and not from humans or the church. In this case, the church is not the creator of the mission but rather an agent of mission Dei, with its involvement in God's ongoing work of salvation for the world. In this article, the author uses a qualitative approach with a literature study method, by examining the origins of the concept of mission Dei, the purpose and content of its news, how mission Dei is with the identity of the church, and its role in the context of the local church. This article with the results of its study shows how the church, especially the local church, is called to be an agent of mission Dei with its evangelistic mission of forming a missionary church, serving (diakonia), and implementing it for the local church in realizing and carrying out God's mission in church service and in society.